Screening of Anti-Lipase Components of Artemisia argyi Leaves Based on Spectrum-Effect Relationships and HPLC-MS/MS - Chang, Yaqing; Zhang, Dan; Yang, Guiya; Zheng, Yuguang; Guo, Long (Frontiers in Pharmacology, 2021)
Pancreatic lipase is a primary lipase critical for triacylglyceride digestion in humans and is considered as a promising target for the treatment of metabolic disorders. Naturally occurring phytochemicals are promising sources of pancreatic lipase inhibitors. The dried leaves of Artemisia argyi H.Lév. & Vaniot (AL), which is widely distributed in China and other Asian countries and has been used as herbal medicine or food supplement for hundreds of years. AL mainly contains essentialvolatile oils, phenolic acids, flavonoids and terpenoids, which exhibit many pharmacological activities such as anti-inflammatory, antioxidant, antimicrobial, analgetic, anti-cancer, anti-diabetes and immunomodulatory effects. However, the anti-lipase activity of AL was lack of study and the investigation of anti-lipase compounds from AL was also insufficient. In the present study, the anti-lipase activity of AL was evaluated in vitro and the potentially pancreatic lipase inhibitors of AL were investigated. High performance liquid chromatography was used to establish fingerprints of AL samples, and fifteen peaks were selected. A pancreatic lipase inhibition assay was performed to evaluate the anti-lipase activity of AL samples. Then, the spectrum-effect relationships between fingerprints and pancreatic lipase inhibitory activity were investigated to identify the anti-lipase constitutes in AL. As the results, four caffeoylquinic acids, which were identified as neochlorogenic acid, chlorogenic acid, isochlorogenic acid B, and isochlorogenic acid A by high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry, were selected as potential pancreatic lipase inhibitors in AL. Moreover, anti-lipase activity evaluation and docking studies of the four compounds was carried out to validate the candidate lipase inhibitors in AL. The results revealed that the four caffeoylquinic acids in AL as potential active constituents displayed with anti-lipase activity. The present research provided evidences for the anti-lipase activity of AL, and suggested that some bioactive compounds in AL could be served as lead compounds for the development of new pancreatic lipase inhibitors.